2006
DOI: 10.1111/j.1399-302x.2006.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis lipids and diseased dental tissues

Abstract: Subgingival plaque, subgingival calculus, diseased teeth, and gingival tissue are contaminated with phosphorylated dihydroceramides produced by P. gingivalis. The previously reported biological activity of these substances together with the recovery of these lipids at periodontal disease sites argues strongly for their classification as virulence factors in promoting chronic inflammatory periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 11 publications
3
51
0
1
Order By: Relevance
“…Several plausible mechanisms could account for periodontal tissue contamination with lipids of P. gingivalis, including direct adhesion between bacteria and host epithelial cells in the gingival sulcus surrounding each tooth (20)(21)(22)(23), direct contact between host tissues and lipid-contaminated diseased teeth, or invasion of periodontal tissues by P. gingivalis (24)(25)(26)(27)(28)(29)(30)(31). Because complex lipids of P. gingivalis are most prevalent on periodontally diseased tooth roots (3,9), this study exposed gingival fibroblasts to lipid films that recreate the approximate lipid levels observed on calculus-contaminated tooth roots. A previous report indirectly estimated P. gingivalis lipid levels on calculus-contaminated tooth roots by quantifying 3-OH iso C 17:0 on root sections of known surface area (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several plausible mechanisms could account for periodontal tissue contamination with lipids of P. gingivalis, including direct adhesion between bacteria and host epithelial cells in the gingival sulcus surrounding each tooth (20)(21)(22)(23), direct contact between host tissues and lipid-contaminated diseased teeth, or invasion of periodontal tissues by P. gingivalis (24)(25)(26)(27)(28)(29)(30)(31). Because complex lipids of P. gingivalis are most prevalent on periodontally diseased tooth roots (3,9), this study exposed gingival fibroblasts to lipid films that recreate the approximate lipid levels observed on calculus-contaminated tooth roots. A previous report indirectly estimated P. gingivalis lipid levels on calculus-contaminated tooth roots by quantifying 3-OH iso C 17:0 on root sections of known surface area (9).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated that P. gingivalis synthesizes two major phosphorylated dihydroceramides, one of which potentiates interleukin-1 (IL-1)-mediated prostaglandin E 2 (PGE 2 ) secretory responses in gingival fibroblasts and markedly alters gingival fibroblast morphology in culture (1). These lipids are also recovered from diseased tooth roots (2), and indirect evidence indicates that the phosphoglycerol dihydroceramide lipids are the primary ceramides of P. gingivalis recovered in gingival tissues at disease sites (3). Therefore, P. gingivalis produces biologically active complex lipids that are recovered at periodontal disease sites.…”
mentioning
confidence: 99%
“…Histological section of a human tooth root showed that calculus is covered with viable bacterial plaque [34]. Nichols et al reported that the dihydroceramide lipids produced by P. gingivalis were found in subgingival calculus [39]. Hence, the presence of calculus will be a secondary etiological factor.…”
Section: Calculus Formationmentioning
confidence: 99%
“…Supragingival calculus may contribute to development of gingival recession [2], and teeth positive for subgingival dental calculus experience a greater rate of clinical periodontal attachment loss in teenagers [3] and patients with untreated chronic or aggressive periodontitis [4,5]. However, the periodontopathic potential of dental calculus stems largely from unmineralized disease-associated bacterial biofilms coating its outer surfaces and nested within its structural lacunae and porosities [6,7], since dental calculus itself exhibits negligible pathogenicity when sterilized free of living microorganisms [8], and can even provide an adherent surface for junctional epithelium when disinfected [9].…”
Section: Introductionmentioning
confidence: 99%